Migration and transformation of three nitrogen in groundwater and antipollution effect of aquitard in North China Plain typical area. Issue 1 (April 2021) - Zhao, Yanjie; Deng, Yirong; Lu, Haijian; Lv, Mingchao; Cheng, Zhou
Abstract: The "three nitrogen" (NH4 + -N, NO2 — N, NO3 − -N) pollution of groundwater in north China plain region endanger the groundwater ecological environment. In this study, we chose the typical area of North China Plain as the representative research area. By numerical method, we analyzed the migration characteristics of "three nitrogen" pollutants in the 200 year time scale in different representative strata structural modes of shallow groundwater system in this area. Based on the simulation results, the retardant ability of the unit thickness of aquitard was analyzed. The results were as follows: 1 The migration of different kinds of "three nitrogen" pollutants in the aquifer system were different; (2) The strata structural characteristics have obvious effects on the migration of "three nitrogen", and their influence rules were different. The three representative strata structure models were constructed on the basis of comprehensive analyzing the regional strata features. Therefore, the simulation results have reference value for evaluation of the "three nitrogen" migration and the retardant ability of the aquitard in this area.